Facilitated intracellular delivery of peptide-guided nanoparticles in tumor tissues - Kim, Jong-Ho; Bae, Sang Mun; Na, Moon-Hee; Shin, Hyeri; Yang, Yu Jin; Min, Kyung Hyun; Choi, Ki Young; Kim, Kwangmeyung; Park, Rang-Woon; Kwon, Ick Chan; Lee, Byung-Heon; Hoffman, Allan S.; et al. (ELSEVIER, 2012)
Macromolecular nanoparticles can extravasate and accumulate within tumor tissues via the passive targeting system, reflecting enhanced permeability and the retention effect. However, the unsatisfactory tumor therapeutic efficacy of the passive-targeting system, attributable to the retention of extravasated nanoparticles in the vicinity of tumor vessels, argues that a new system that facilitates intracellular delivery of nanoparticles within tumors is needed. Here, we developed hydrophobically modified glycol chitosan (HGC) nanoparticles conjugated with interleukin-4 receptor (IL-4R) binding peptides, termed I4R, and tested them in mice bearing IL-4R-positive tumors. These HGC-I4R nanoparticles exhibited enhanced IL-4R-dependent cellular uptake in tumors compared to nonconjugated nanoparticles, leading to better therapeutic and imaging efficacy. We conclude that I4R facilitates and enhances cellular uptake of nanoparticles in tumor tissues. This study suggests that the intracelluar uptake of nanoparticles in tumors is an essential factor to consider in designing nanoparticles for tumor-targeted drug delivery and imaging. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: GLYCOL CHITOSAN NANOPARTICLES; INTERLEUKIN-4 RECEPTOR; CANCER-THERAPY; AFFINITY; INTERNALIZATION; LOCALIZATION; CHEMOTHERAPY; VASCULATURE; DOXORUBICIN; EXPRESSION